NEED ANALYSIS OF INTERACTIVE MULTIMEDIA DEVELOPMENT WITH CONTEXTUAL APPROACH ON POLLUTION MATERIAL - Sevie Safitri Rosalina; Andi Suhardi (Science Education, Institut Agama Islam Negeri Ponorogo, 2020)
This study aims to find out information related to the needs of interactive multimedia with a contextual approach as a science learning media. This research is a research and development that refers to the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). Data collection techniques used were questionnaires, observations, and interviews and relevant literature studies. The population in this study is SMP Negeri 1 Jember. The samples in this study were 80 students of class VII and teachers of natural science subjects. Data were analyzed using descriptive analysis. The results of this study were obtained that the learning media used are still limited to textbooks and worksheets and there is no use of interactive multimedia so it is necessary to do interactive multimedia development on natural science materials especially environmental pollution materials that are appropriate to the needs of students in order to achieve learning objectives. Based on this it can be concluded that interactive multimedia with a contextual approach is needed to be developed in natural science subjects.